2022
DOI: 10.1136/bmjopen-2021-056720
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound measurements of pathological and physiological skin thickness: a scoping review protocol

Abstract: IntroductionUltrasound is a quick, safe, and non-invasive imaging method that can be used to measure skin thickness in pathological cutaneous conditions in clinical and research settings. Despite widespread use, there exists a lack of standardisation and reporting of ultrasound skin thickness measurement methods, which makes between-studies comparisons difficult. To address this, we present a scoping review protocol, which aims to determine what is and is not known about the measurement of skin and scar thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…The protocol for this review has been published a priori 37. This scoping review was conducted and is reported according to the framework by Arksey and O’Malley 38.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for this review has been published a priori 37. This scoping review was conducted and is reported according to the framework by Arksey and O’Malley 38.…”
Section: Methodsmentioning
confidence: 99%
“…A lot of devices may incorporate color Doppler analysis for the characterization of blood flow and vessel morphology within the suspected skin lesions [ 112 ]. Regarding the amplitude mode (A-mode), the computer generates a one-dimensional line graph that can be used to interpret echogenicity at various distances from the probe [ 112 , 113 ]. The so-called echogenicity represents the internal echo pattern—or the ability of a structure to reflect sound waves relative to its surrounding tissue [ 114 ].…”
Section: Anatomical Imaging Techniquesmentioning
confidence: 99%
“…[5] Po raz pierwszy USG w dermatologii zastosowali Alexander i Miller w 1979 roku do pomiaru grubości ludzkiej skóry -zastosowane wówczas częstotliwości (15MHz) nie pozwalały na rozróżnienie poszczególnych jej warstw, ale dało to początek dalszym badaniom w tym obszarze. [3,6] Jednakże, dynamiczny rozwój ultrasonografii skóry rozpoczął się na przełomie XX i XXI wieku, co było zasługą postępu w nowych technologiach komputerowych. Przełomem było wprowadzenie ultrasonografii wysokich częstotliwości.…”
Section: Ultrasonografia Wysokich Częstotliwości (Hf-usg) Wykorzystuj...unclassified